2023
DOI: 10.2147/ijn.s389535
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Metabolomics Analysis Reveals the Toxicity of ZnO Quantum Dots on Human SMMC-7721 Cells

Abstract: Purpose ZnO quantum dots (QDs) are composed of less toxic metals than other QDs but have the same interesting photochemical properties. Thus, they have received considerable attention recently. Nevertheless, their toxicity cannot be ignored. Methods In this study, we incubated ZnO QDs with human SMMC-7721 cells for 24 h to assess their nanotoxicity through proteomics (Fold change >1.5 and p -value <0.05) and metabolomics (Fold change ≥ 1.5; VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that previous studies have shown that exposure to a wide range of inorganic ENMs, including titanium dioxide, gold, silver, and copper nanoparticles, could be associated with perturbations of basic metabolic pathways such as those involved in bioenergetics, biosynthesis, and redox reactions in different experimental models [ 33 , 34 , 35 , 36 ]. Furthermore, it has been demonstrated that exposure to ENMs could disturb key cellular pathways, including apoptosis, ferroptosis, redox homeostasis, energy metabolism, mitochondrial function, and inflammatory responses [ 49 , 50 , 51 ]. To the best of our knowledge, this is the first study that assessed metabolomic changes at low and subtoxic concentrations of ZnONPs and NiONPs.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that previous studies have shown that exposure to a wide range of inorganic ENMs, including titanium dioxide, gold, silver, and copper nanoparticles, could be associated with perturbations of basic metabolic pathways such as those involved in bioenergetics, biosynthesis, and redox reactions in different experimental models [ 33 , 34 , 35 , 36 ]. Furthermore, it has been demonstrated that exposure to ENMs could disturb key cellular pathways, including apoptosis, ferroptosis, redox homeostasis, energy metabolism, mitochondrial function, and inflammatory responses [ 49 , 50 , 51 ]. To the best of our knowledge, this is the first study that assessed metabolomic changes at low and subtoxic concentrations of ZnONPs and NiONPs.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of metabolomics is that information on a large number of metabolites could be obtained through a single measurement, an oftentimes-basic requirement for rapidly understanding the level of drug toxicity. A large-scale screening of drugs or chemical compounds can be achieved through in vitro metabolomics approaches [169][170][171].…”
Section: Toxicity Assessmentmentioning
confidence: 99%
“…One important use of in vitro metabolomics, which employs cell lines, primary cells, co-cultures in 2D or 3D format, etc., is to predict toxicological patterns of unknown chemicals in the biological system using known reference chemicals [170,172]. Such analysis starts with the comparison of a metabolic profile of a known reference chemical with its toxicological profile in vivo.…”
Section: Toxicity Assessmentmentioning
confidence: 99%